Pregnancy and Birth Outcomes in the United States. Issue 3 (May 2023) - Wisner, Kirsten
Abstract : Our maternity nursing expert, Dr. Wisner, explains the findings and implications of the March of Dimes (2022) Report Card: Stark and Unacceptable Disparities Exist Alongside a Troubling Rise in Preterm Birth Rates. Preterm birth rates are rising again and disparities in outcomes continue in the United States.